THE IMPLEMENTATION OF MOBILE GAMES IN READING COMPREHENSION AT SMPN 1 BANDARLAMPUNG - Yanuarius Yanu Dharmawan; Maully Reighita Almega (Universitas Bandar Lampung, 2020)
This research is quantitative research. The objectives of study were to investigate the process of usingmobile games in reading comprehension and to analyze how the effects of mobile games on readingcomprehension of the IX grade students at SMP N 1 Bandar Lampung in ESL context. Besides, it was tofind out whether students are motivated to learn ESL by using mobile phone. The subject of research was25 students at SMPN 1 Bandar Lampung. The instrument of research was reading comprehension test.The results showed that the students enjoyed the process as they played mobile games since it could taketheir interest in learning English and the mobile games could give positive effect on students’ readingcomprehension. In addition, students are motivated to understand the storyline of the game which then